Some Correlation Studies of the Rooting System of Cedrus deodara in Chachpur (Himachal Pradesh) - Suri, S. K. (Indian Forester, 1969)
This paper deals with the study undertaken in Chachpur compartment 13 of Pabar Valley Division (Himachal Pradesh) to find out the relationships between diameter, height, crown projection area, root spread area and root depth of standing and naturally uprooted deodar trees. A positive correlation was observed between these characters. The ratio between crown projection area and root spread area is about 5, and between height and root depth about 17 thereby suggesting that a precise knowledge about these relationships will prove of great practical value in predicting the site quality and minimum exploitable soil depth, in making the choice of species and deciding the initial spacing to be adopted for a plantation, in evolving suitable stand density indices and in deciding the method of fertilizer application.